2018
DOI: 10.3892/ol.2018.8712
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid and Sennoside B inhibit osteosarcoma cell migration, invasion and growth by repressing the expression of c‑Jun

Abstract: Osteosarcoma is a mesenchymally derived, high-grade bone sarcoma that is the most frequently diagnosed primary malignant bone tumor. Today, chemoprevention is regarded as a promising and realistic approach in the prevention of human cancer. Previous studies have suggested ellagic acid (EA) and Sennoside B have potential in this regard. The aim of the present study was to elucidate the anti-osteosarcoma effects of EA and Sennoside B by using Saos-2 and MG63 osteosarcoma cells. It was identified that EA or Senno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…14 The anticarcinogenic effect of EA has been shown in some types of tumors, including prostate cancer, lung cancer, osteosarcoma, breast cancer, and so forth. [15][16][17][18] Consistent with previous studies, EA also showed good antitumor activity in ESCC. We found that EA inhibited ESCC cell survival by inducing cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…14 The anticarcinogenic effect of EA has been shown in some types of tumors, including prostate cancer, lung cancer, osteosarcoma, breast cancer, and so forth. [15][16][17][18] Consistent with previous studies, EA also showed good antitumor activity in ESCC. We found that EA inhibited ESCC cell survival by inducing cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…Exposure of the human osteosarcoma Saos-2 and MG63 cell lines to EA resulted in a marked inhibition of cell proliferation, with G1 phase arrest, as a consequence of reduced c-Jun expression. In addition, inhibition of cell migration and invasion was observed, suggesting that EA might exert antimetastatic effects [ 124 ]. These finding are particularly relevant, since metastasis remains the most important fatal complication of osteosarcoma.…”
Section: In Vitro and In Vivo Activity Of Ellagic Acid In Differenmentioning
confidence: 99%
“…[12][13][14][15] Furthermore, many studies have reported that inhibition of cell migration decreases tumor growth in multiple cancers. [16][17][18] Therefore, it is important to elucidate the cellular basis and molecular mechanisms of β 2 -GPI function in antitumorigenesis. The present study aims to explore the specific regulatory domain and intracellular signaling of β 2 -GPI with a potential for antimelanoma progression.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that abnormal cell migration and proliferation are closely related to carcinogenesis . Furthermore, many studies have reported that inhibition of cell migration decreases tumor growth in multiple cancers . Therefore, it is important to elucidate the cellular basis and molecular mechanisms of β 2 ‐GPI function in antitumorigenesis.…”
Section: Introductionmentioning
confidence: 99%